2017
DOI: 10.1007/s00248-017-1065-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Synergistic Effect of Antifungal Volatile Organic Compounds Emitted by the Geotrichum candidum PF005, an Endophytic Fungus from the Eggplant

Abstract: Plant-associated endophytes are recognized as sources of novel bioactive molecules having diverse applications. In this study, an endophytic yeast-like fungal strain was isolated from the fruit of eggplant (Solanum melongena) and identified as Geotrichum candidum through phenotypic and genotypic characterizations. This endophytic G. candidum isolate PF005 was found to emit fruity scented volatiles. The compositional profiling of volatile organic compounds (VOCs) revealed the presence of 3-methyl-1-butanol, eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Healthy Ginkgo leaves were washed under running tap water, cut into 3 mm × 3 mm pieces with a scalpel, surface sterilized by immersion in 75% ethanol for 60 s, 2% NaClO solution for 180 s, and rinsed with sterile distilled water for three times between solutions and at the end. All steps were carried out under aseptic conditions and finally dried . Four pieces were placed onto potato dextrose agar (PDA) supplemented with an antibiotic (chloramphenicol; 250 mg/L).…”
Section: Methodsmentioning
confidence: 99%
“…Healthy Ginkgo leaves were washed under running tap water, cut into 3 mm × 3 mm pieces with a scalpel, surface sterilized by immersion in 75% ethanol for 60 s, 2% NaClO solution for 180 s, and rinsed with sterile distilled water for three times between solutions and at the end. All steps were carried out under aseptic conditions and finally dried . Four pieces were placed onto potato dextrose agar (PDA) supplemented with an antibiotic (chloramphenicol; 250 mg/L).…”
Section: Methodsmentioning
confidence: 99%
“…showed 100% inhibition of R. solani growth (Figure 1). In comparison, Mookherjee et al found that the endophyte Geotrichum candidum utilized different carbon sources to varying extents [23], and the antifungal activity of its VOCs against phytopathogen R. solani changed with each carbon source, with the maximum mean growth inhibition of about 62% observed with glucose. Elkahoui et al (2015) found 25 VOCs producing strains inhibited (by 27-50%) the growth of R. solani [24].…”
Section: Discussionmentioning
confidence: 99%
“…Compound`s identification was done by comparison of the mass spectra obtained for each compound with the one reported in mass spectral libraries [30], including NIST 05 and NIST 27 (National Institute of Standards and Technology, Gaithersburg, USA). Additionally, Kovats index was calculated for each compound using a mixture of saturated n-alkanes C7-C30 (Sigma-Aldrich ® ), followed by comparison with literature data [30,31,32].…”
Section: Mvocs Analysis By Gc-msmentioning
confidence: 99%
“…The relative concentrations of the constituents are represented in the loadings graph (Figure 6b) by circles with three different colors, where red, dark blue and light blue are associated to the highest concentration constituents from the actinobacteria (ACTB-77), C. musae and co-culture, respectively. Figure 6b shows 3-methyl-butan-1-ol (1), 2-methyl-butan-1-ol (2), α-phellandrene (12), β-phellandrene (15), phenylethyl alcohol (24), p-mentha-1,5-dien-8-ol (29), menthol (31) and aristolochene (59) as constituents from the C. musae group with the highest relatively concentrations. Among them, compounds 1, 12, 15, 24 and 59 represent ca.…”
Section: Actb-77 C Musae and Their Co-culturementioning
confidence: 99%